PENGARUH APLIKASI PUPUK KANDANG, NPK DAN URINE KELINCI TERHADAP PERTUMBUHAN DAN PRODUKSI DUA MACAM VARIETASTANAMAN MENTIMUN (Cucumis sativus .L) - Tri Handayani; Anis Sholihah; Siti Asmaniyah (AGRONISMA, 2020)
This research aims: 1. Knowing the differences in the provision of manure, POC and NPK on the growth of cucumber plants. 2. Knowing the differences in the provision of manure, POC, and NPK to the production of cucumber plants. 3. Knowing the differences in the provision of manure, POC and NPK on the quality of cucumber plants. The research was conducted on May 31 - August 22, 2019, and took place in the Tlogo Warna Block C Road, Tlogomas Village, Lowokwaru District, Malang. Altitude ± 900 meters above sea level, the average temperature of 240C. rainfall 2000-3000 / year and soil type. In this study using a Factorial Randomized Block Design with control consisting of 2 factors, Factor 1 is the type of fertilizer: P1 = NPK fertilizer (16:16:16), P2 = chicken manure, P3 = POC rabbit urine. Factor 2 is Variety Varieties, V1 = Variety Vanesa, V2 = Hybrid F1 Monroe variety Of the two factors obtained 6 combinations added 1 control treatment so that there are 7 treatments. Each treatment was repeated 3 times using 6 samples for each treatment. the administration of POC rabbit urine showed the best results on the growth of cucumber plants, namely the plant length and stem diameter with results of 132.78 cm and 0.31 cm, respectively, compared with the provision of chicken manure and NPK pearls. The application of pearl NPK fertilizer (16:16:16) gives a very good production yield on V2 (Hybrid F1 variety monroe). With an average total weight per bed in harvest 1 is 3018.33 kg and harvest 2 is 1986.33 kg / bed. The provision of manure, rabbit urine POC and NPK had no significant effect on the quality of cucumber plants.